A flexible approach to estimate the equity premium. Issue 59 (20th December 2017) - Bonaparte, Yosef; Fabozzi, Frank J
ABSTRACT: In this article, we estimate the risk aversion for households accounting for their lifetime consumption risk. Households take into account the overall lifetime uninsured consumption risk when optimizing their resources, which based on micro data varies across households. Thus, representing households' consumption by merging cross-sectional micro data into the single Euler equation (the common approach for estimating risk aversion based on consumption-based asset pricing theory) may be too rough an approximation, leading to biased results with respect to risk aversion. Our results suggest that consumption-based asset pricing models that were rejected in several studies do in fact fit the data when we account for households' lifetime consumption risk. This finding also has implications for long-run aggregate consumption-based asset pricing models.